2021
DOI: 10.3389/fcell.2021.684036
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Alterations in Preneoplastic Development Revealed by Untargeted Metabolomic Analysis

Abstract: Metabolic rewiring is a critical hallmark of tumorigenesis and is essential for the development of cancer. Although many key features of metabolic alteration that are crucial for tumor cell survival, proliferation and progression have been identified, these are obtained from studies with established tumors and cancer cell lines. However, information on the essential metabolic changes that occur during pre-neoplastic cell (PNC) development that enables its progression to full blown tumor is still lacking. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…In our model of tumour initiation, human HRAS G12V (thereafter HRAS) was induced in zebrafish larval keratinocytes to mimic the initial mutational event leading to PNC development (Figure 1 A Schematic). EGFP tagged PNCs can be identified from 8 hours post induction (hpi) and analysing cell proliferation suggests that enhanced PNC growth is overt from 24hpi and the proliferation rate in PNCs remains high at later times 10,11 . We therefore focused our analysis within the first 24 hours of PNC emergence to establish the earliest metabolic changes following PNC induction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our model of tumour initiation, human HRAS G12V (thereafter HRAS) was induced in zebrafish larval keratinocytes to mimic the initial mutational event leading to PNC development (Figure 1 A Schematic). EGFP tagged PNCs can be identified from 8 hours post induction (hpi) and analysing cell proliferation suggests that enhanced PNC growth is overt from 24hpi and the proliferation rate in PNCs remains high at later times 10,11 . We therefore focused our analysis within the first 24 hours of PNC emergence to establish the earliest metabolic changes following PNC induction.…”
Section: Resultsmentioning
confidence: 99%
“…The zebrafish lines used in this study include Tg(krtt1c19e::KalTA4-ER T2 ; cmlc2::eGFP) ed201 (hereafter K19 Gal4 driver) primarily drives basal keratinocytes. Tg(krt4::KalTA4-ER T2 ; cmlc2::eGFP) ed202 (hereafter K4 Gal4 driver) primarily expressed in superficial keratinocytes 40 Tg(UAS::eGFP-HRAS G12V ; cmlc2::eGFP) ed203 (hereafter UAS:RAS) 11 . Tg(UAS::eGFP-CAAX; cmlc2::eGFP) ed204 (hereafter UAS:CAAX) 11…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results highlight the importance of a good and efficient data preprocessing step in lipid annotation, especially when a complex third dimension is added to the analysis. PNNL Pre-Processor has also been used in other lipidomic studies within the last 2 years for demultiplexing and saturation repair [65][66][67][68][69][70], which shows a good acceptance of the software for these studies using IM-MS.…”
Section: Demultiplexing and Other Pre-processing Toolsmentioning
confidence: 99%
“…In a seminal article, Sivanand and Heiden reviewed the fundamental perspectives concerning the critical role of BCAA metabolism in cancer ( 143 ). Indeed, metabolism is altered in various diseases, including cancer ( 144 , 145 ). Interestingly, Mayers et al reported elevations in circulating BCAAs during pancreatic cancer progression in humans and mouse cancer models ( 146 ).…”
Section: Mtorc1 and Branched-chain Amino Acidsmentioning
confidence: 99%